EKSISTENSI HUBUNGAN NEGARA DENGAN BADAN HUKUM SWASTA DALAM PENGELOLAAN MIGAS DI INDONESIA - Desy Ratnasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Indonesia is a welfare state, the legal basis for oil and gas management must be in accordance with and in sync with the oil and gas management system which is in accordance with Article 33 of the Republic of Indonesia Constitution and the Oil and Gas Law. The existence of state relations with private legal entities in the oil and gas management system in Indonesia places the state in an equal position with private business entities, in this case the relationship between the state and private legal entities is seen as degrading the status of the state. The research method used is normative/doctrinal legal research and the research approach uses a conceptual approach that examines the literature or literature that is closely related to the problem under study.